Spatio-temporal dynamics of rabies and habitat suitability of the common marmoset Callithrix jacchus in Brazil - Benavides, Julio A. [UNESP]; Raghavan, Ram K.; Boere, Vanner; Rocha, Silene; Wada, Marcelo Y.; Vargas, Alexander; Voietta, Fernanda; E Silva, Ita de Oliveira; Leal, Silvana; de Castro, Alene; Arruda, Maria de Fatima; Peterson, A. Townsend; et al. (Public Library of Science (PLoS), 2022)
Rabies transmitted by wildlife is now the main source of human rabies in the Americas. The common marmoset, Callithrix jacchus, is considered a reservoir of rabies causing sporadic and unpredictable human deaths in Brazil, but the extent of the spillover risk to humans remains unknown. In this study, we described the spatiotemporal dynamics of rabies affect-ing C. jacchus reported to Brazil’s Ministry of Health passive surveillance system between 2008 and 2020, and combined ecological niche modelling with C. jacchus occurrence data to predict its suitable habitat. Our results show that 67 outbreaks (91 cases) of rabies affect-ing C. jacchus were reported by 41 municipalities between January 2008 and October 2020, with a mean of 5 outbreaks/year [range: 1–14]. The maximum number of outbreaks and municipalities reporting cases occurred in 2018, coinciding with higher surveillance of primate deaths due to Yellow Fever. A mean of 3 [1–9] new municipalities reported outbreaks yearly, suggesting potential spatial expansions of the C. jacchus variant in northeastern Brazil and emerging rabies spillover from vampire bat Desmodus rotundus to C. jacchus in the north and south. Outbreaks were concentrated in the states of Ceará (72%) and Pernam-buco (16%) up to 2012, but are now reported in Piauí since 2013, in Bahia since 2017 (D. rotundus’ antigenic variant, AgV3) and in Rio de Janeiro since 2019 (AgV3). Besides confirming suitable habitat for this primate in the northeast and the east coast of Brazil, our Maximum Entropy model also predicted suitable habitat on the north and the west states of the country but predicted low habitat suitability among inland municipalities of the Caatinga biome reporting rabies. Our findings revealed new areas reporting rabies infecting C. jac-chus, highlighting the need to implement strategies limiting spillover to humans and to better understand the drivers of C. jacchus rabies dynamics.